Gridded hourly physical oceanography data from hydrographic moorings in the eastern Fram Strait between 1997 - 2024 - Rebecca McPherson; Wilken-Jon von Appen; Mario Hoppmann; Normen Lochthofen; Matthias Monsees; Carina Engicht; Torsten Kanzow; Thomas Soltwedel; Katja Metfies; Agnieszka Beszczynska-Möller; Ursula Schauer; Eberhard Fahrbach (PANGAEA, 2025)
The collection contains time series data of physical oceanographic parameters (temperature, salinity, and depth) which were collected from moorings F1 to F7 in the eastern Fram Strait between August 1997 and July 2024. From August 1997 to July 2016, the moorings F1 through F7 were deployed along a zonal section at approximately 78°50 extquotesingleN, spanning 4°E to 9°E. In July 2016, the array was shifted northward to 79°N, and the horizontal extent was reduced. Since then, the mooring configuration has included F1, F2, F3, F4, F5, and HG-IV (referred to as F6 in this dataset for consistency). Mooring F7 was discontinued after 2015, and no data is available from F7 beyond that year. The repositioning was done such that the moorings remained approximately on the same isobath and would capture a similar current structure of the WSC. The mooring setup has evolved over time, with an increasing number of instruments deployed since the initial array configuration. When available, all moorings recorded temperature and salinities at five standard depths: 75?m, 250?m, 750?m, 1000?m, and near the seafloor. Temperature and salinity were measured using Sea-Bird sensors (SBE56, SBE37, SBE16; Sea-Bird Electronics Inc.) at intervals ranging from 10 minutes to 2 hours. Gridding: Hourly averages of temperature and salinity from each instrument were vertically interpolated onto a uniform grid with 4 m vertical resolution. Where pressure sensors were available, measurements were accurately mapped to their actual depths, allowing correction for vertical mooring motion (knockdowns). For earlier deployments (prior to 2010), some instruments did not include pressure sensors and were therefore assigned to fixed nominal depths. In such cases, uncorrected mooring knockdowns may have led to deeper water being attributed to shallower depth levels. Missing data: Due to occasional instrument and mooring failures, continuous records are not available at all standard depths and locations. Where data was missing, it was replaced by reconstructed data (XR), composed of the sum of three components of the measured data: XR = Xmean + Xseason + Xtrend where the long-term mean (Xmean), a seasonal cycle (Xseason) and a linear trend (Xtrend) were calculated from the measured data at each standard depth. The linear trend and mean were calculated for each decade due to multidecadal variability, i.e., between 1997 - 2007; 2007 - 2017; and 2017 - 2024. Due to the vertical motions, these components were calculated over a depth range about the standard depth (i.e., 75 ± 25 m; 250 ± 50 m; 750 ± 50 m; 1500 ± 100 m; near bottom ± 100 m). Interpolation: All data was linearly interpolated vertically from the deepest original measurement to either the surface for temperature where satellites provided data, or to the shallowest of either 50m or the depth of the upper measurement for salinity. A logic matrix for each variable indicates observed (measured) data as 1, while 0 indicates reconstructed or interpolated data.